(untitled) (Global Journal of Science Frontier Research, 2014)
In the Northern highlands of Ethiopia, surface runoff and soil loss have been identified as critical problems and the most limiting factors in agricultural production. Although different soil and water conservation mesures have been constructed by mobilizing the communities and resources, runoff has continued and put extra pressure on the structures. This study was initiated to investigate surface runoff and soil loss as affected by integration of conservation tillage with fanya juus’ at plot level at Enerata kebele, East Gojjam Zone of Amhara Region. There were two tillage treatments (CT and TT) combined with newly constructed fanya juus with four replications. Runoff and soil loss were recorded at 38 rainfall event through three tied trenches within wheat (triticum vulgare) and tef (eragrostis tef) farm plots. Result showed that average runof f coefficients of 17.72% and 43.96% were recorded due to conservation tillage system from wheat and tef farm plots, respectevly. Thus, runoff coefficient induced 0.54 and 0.18 times reduced in soil loss from wheat and tef plots, respectively. Reduction of runoff volume and soil loss in the conservation tillage systems were attributed to retarded movement of water in the presence of invisible barriers in each furrow that are laid along the contour. The retarded movement of water resulted in increased infiltration and reduced soil loss. Overall, conservation tillage system has a paramount importance in reduction of soil loss while integrated with fanya juus’ structures in cultivated lands.